Diversification of batik jarum handicraft art product to solidify community based creative economic development in Klaten regency / Margana - Margana, Margana (2016)
This research aims; to explore the potential development of batik Jarum handicraft art as one of local superior commodity in Klaten regency; to study the constraints encountered by the batik Jarum community, both employers and craftsperson, in developing batik handicraft art; to analyze the contribution of Batik Jarum production to reinforcing the communitybased creative economy in Klaten Regency; to find out the diversification of batik Jarum production the Batik Jarum community has done; to find out the Klaten Regency Government’s policy and program in developing Batik Jarum potency to support the community-based creative economic development; This study is a descriptive research with qualitative approach. The data of research will be collected using some methods: field observation, interview, Focus Group Discussion, and documentation. To obtain data validity, source triangulation will be used. Data will be analyzed using an interactive technique of analysis and thematic analysis. Conclude this research are; Batik Jarum has a high diversity of products, because the number of UKM and craftsmen who are in the village of Jarum, they race for innovation and creation; Barriers faced by community batik Jarum is limited product diversification, the competence of UKM and craftsmen to create and innovate, equipment, and marketing strategies; Batik Jarum production contributes to the strengthening of the creative economy can support local economic development through job creation and the improvement of people’s income; Although still limited, batik Jarum community has diversified in terms of the manufacturing techniques, motifs, colors, media, and design; Policies and programs Klaten regency in developing batik Jarum craftsmen is sending for training, study visits, internships and exhibitions in order to improve their competence.